Some Upper Cretaceous ammonites from the Nacatoch Sand of Hempstead County, Arkansas - Cobban, W; Kennedy, W (1991)
Richly fossiliferous concretions from the middle, glauconitic member of the Nacatoch Sand of southwestern Arkansas include an ammonite assemblage here referred to as the Nostoceras (Nostoceras) rugosum zone. The index species is abundant, accompanied by Solenoceras texanum (Shumard, 1861), S. nitidum Cobban, 1974, and Parasolenoceras pulcher n.sp., all of which are described and illustrated; also present, but not described, are Scaphites (Scaphites) aff. pumilis Stephenson, 1941 and Baculites claviformis Stephenson, 1941. -Authors